Dose–response relationships of sarcopenia parameters with incident disability and mortality in older Japanese adults. Issue 2 (25th February 2022) - Seino, Satoshi; Kitamura, Akihiko; Abe, Takumi; Taniguchi, Yu; Murayama, Hiroshi; Amano, Hidenori; Nishi, Mariko; Nofuji, Yu; Yokoyama, Yuri; Narita, Miki; Shinkai, Shoji; Fujiwara, Yoshinori
Abstract: Background: Sarcopenia‐related parameters may have differential impacts on health‐related outcomes in older adults. We examined dose–response relationships of body composition, muscle strength, and physical performance with incident disability and mortality. Methods: This prospective study included 1765 Japanese residents (862 men; 903 women) aged ≥65 years who participated in health check‐ups. Outcomes were incident disability and all‐cause mortality. Fat mass index (FMI) and skeletal muscle mass index (SMI), determined using segmental multi‐frequency bioelectrical impedance analysis, handgrip strength (HGS), and usual gait speed (UGS) were measured. We determined multivariate‐adjusted hazard ratios (HRs) for disability and mortality relative to sex‐specific reference values (FMI: medians; SMI: 7.0 kg/m 2 for men and 5.7 kg/m 2 for women; HGS: 28 kg for men and 18 kg for women; or UGS: 1.0 m/s for both sexes). Association shapes were examined using restricted cubic splines or fractional polynomial functions. Results: The median follow‐up was 5.3 years; 107 (12.7%) men and 123 (14.2%) women developed disability, and 101 (11.7%) men and 56 (6.2%) women died. FMI did not impact any outcome in men and disability in women, while an FMI ≤ 7.3 kg/m 2 (median) was significantly associated with higher mortality risk in women, compared with median FMI. SMI did not impact disability in either sex and mortality in women, but showed a significant inverse dose–response relationship with mortality risk in men [HRs (95% confidence intervals) of minimum and maximum values compared with the reference value: 2.18 (1.07–4.46) and 0.43 (0.20–0.93), respectively], independent of HGS and UGS. HGS and UGS showed a significant inverse dose–response relationship with disability in both sexes [HGS: 1.71 (1.00–2.91) and 0.31 (0.09–0.99), respectively, in men, 2.42 (1.18–4.96) and 0.41 (0.20–0.85), respectively, in women; UGS: 2.14 (1.23–3.74) and 0.23 (0.08–0.67), respectively, in men, 3.26 (2.07–5.14) and 0.11 (0.05–0.26), respectively, in women] and mortality in women [HGS: 6.84 (2.84–16.47) and 0.06 (0.02–0.21), respectively; UGS: 2.67 (1.14–6.27) and 0.30 (0.11–0.85), respectively], independent of body composition, but did not impact mortality in men. Conclusions: Disability risk was more dependent on muscle strength and physical performance in both sexes. Mortality risk in men was more dependent on muscle mass, and mortality risk in women was influenced by lower fat mass along with muscle strength and physical performance. Although improving muscle strength and physical performance should be the first target for health promotion, it is also necessary to pay attention to body composition to extend life expectancy in older adults.